THE INFLUENCE OF INCOME AND THE LEVEL OF CONGREGANTS' TRUST ON THE INTEREST IN DONATING AT AL AQSHA GRAND MOSQUE KLATEN - Purwanti, Titik (ITB AAS Indonesia Surakarta, 2025)
The purpose of this study is to determine the effect of income and the level of trust of congregants on the interest in giving alms at Al Aqsha Mosque in Klaten. The research method used is a quantitative method. Questionnaires were used to collect data for this investigation. The population is the main focus of the researcher, namely all adult congregants of Al Aqsha Grand Mosque in Klaten. This study used a probability sampling methodology strategy and multivariate analysis. There are thirteen factors examined in this study, including three indicators related to income, seven indicators related to the level of trust, and three indicators related to interest. In this study, the recommended number of sample members is the number of factors studied multiplied by 8, which is 104 respondents. The results of the study indicate that the income variable does not have a significant effect on the interest in giving alms. Meanwhile, the variable of Trust Level partially has a significant effect on the interest in giving alms. It refers to a person's level of trust in relying on others in whom they have confidence. This trust arises from perceptions formed through learning and experience, such as the congregants of Al Aqsha Grand Mosque towards the mosque management. By granting this trust, more congregants entrust their alms for those in need. A high level of trust in the mosque management becomes a factor in an individual's willingness to give alms, and the transparency of the mosque's financial management to the congregants is also an important factor in attracting someone's interest in giving alms.